Analisis Kebijakan Penempatan Jabatan Struktural Organisasi PT. Kanitra Mitra Jayautama, Tenggarong Kalimantan Timur - Jagad, Daniel Jaya; Mujahid , Mujahid (Syntax Literate, 2025)
This study aims to analyze the structural position placement policy at PT. Kanitra Mitra Jayautama (KAMAJU), Tenggarong, East Kalimantan, and identify the supporting and inhibiting factors in its implementation. This research employs a qualitative descriptive and phenomenological approach, focusing on the experiences, perceptions, and opinions of key informants, including human resource management, other staff members, and employees involved in the decision-making process of position placement. The primary data collection methods include in-depth interviews with nine key informants at various levels and direct observations of the placement process. Additional data were gathered from company documents, annual reports, and previous studies. Informants were selected using purposive sampling, encompassing HR managers, supervisors, and employees affected by the placement policy. The data were analyzed qualitatively through transcription, repeated readings, coding, theme identification, and data interpretation. The study found that the position placement policy at PT. KAMAJU is based on the merit system principle, which includes qualification, competence, and performance. However, its implementation has not been fully effective. In terms of qualification, the company has established indicators such as educational background, work experience, and technical competencies as the basis for placement. However, in practice, this policy has not been consistently applied, leading to mismatches between positions and employee competencies. Regarding competence, the company uses Mechanical Grading as part of its internal assessment. However, this process remains highly subjective and does not adequately emphasize soft skills such as leadership and communication. In terms of performance, although some companies use Key Performance Indicators (KPIs) for evaluations, their implementation at PT. KAMAJU is inconsistent. It was observed that some high-performing employees were not promoted, while lower-performing employees received promotions, indicating that promotion decisions were not entirely merit-based.